Roundabout Capacity Estimation Model Considering Driver Behaviour on the Exiting and Entry Flows - Žura, Marijan (Promet - Traffic&Transportation, 2022)
Roundabout capacity estimation has been the subject of several types of research in recent decades. Most of the analyses are based on the empirical or analytical models (e.g. gap acceptance theory) considering various kinds of conflicting flows, namely entry, circulating, and exit-ing flow. The drivers on the exiting flow either obey the traffic rule (use the right-turn indicator) or disobey the traffic rule (do not use the right-turn indicator). Accord-ing to the reviewed literature, the impact of these driv-ers on the roundabout capacity has not been studied to a greater extent. Therefore, this study aims to develop an analytical roundabout capacity estimation model that also takes into account a share of exiting flow. It extends Brilon-Wu’s model, by including the impact of exiting drivers who disobey the traffic rule on the gap accep-tance of the entering drivers. The proposed model was validated using the quasi-observation data generated by a microscopic model. The results obtained by our model were compared with Bovy’ and Yaps’ empirical models as well as Brilon-Wu’s analytical model for a single-lane roundabout. Using the RMSE and regression analysis, it is proved that the proposed model outperforms the exist-ing models in terms of estimating the capacity and delays of roundabouts.